Construction and Evaluation of V. cholerae O139 Mutant, VCUSM21P, as a Safe Live Attenuated Cholera Vaccine - Murugaiah, Chandrika; Nik Mohd Noor, Nik Zuraina; Mustafa, Shyamoli; Manickam, Ravichandran; Pattabhiraman, Lalitha (Public Library of Science (PLoS), 2014)
Cholera is a major infectious disease, affecting millions of lives annually. In endemic areas, implementation of vaccination strategy against cholera is vital. As the use of safer live vaccine that can induce protective immunity against Vibrio cholerae O139 infection is a promising approach for immunization, we have designed VCUSM21P, an oral cholera vaccine candidate, which has ctxA that encodes A subunit of ctx and mutated rtxA/C, ace and zot mutations. VCUSM21P was found not to disassemble the actin of HEp2 cells. It colonized the mice intestine approximately 1 log lower than that of the Wild Type (WT) strain obtained from Hospital Universiti Sains Malaysia. In the ileal loop assay, unlike WT challenge, 16106 and 16108 colony forming unit (CFU) of VCUSM21P was not reactogenic in non-immunized rabbits. Whereas, the reactogenicity caused by the WT in rabbits immunized with 161010 CFU of VCUSM21P was found to be reduced as evidenced by absence of fluid in loops administered with 16102–16107 CFU of WT. Oral immunization using 161010 CFU of VCUSM21P induced both IgA and IgG against Cholera Toxin (CT) and O139 lipopolysaccharides (LPS). The serum vibriocidal antibody titer had a peak rise of 2560 fold on week 4. Following Removable Intestinal Tie Adult Rabbit Diarrhoea (RITARD) experiment, the nonimmunized rabbits were found not to be protected against lethal challenge with 16109 CFU WT, but 100% of immunized rabbits survived the challenge. In the past eleven years, V. cholerae O139 induced cholera has not been observed. However, attenuated VCUSM21P vaccine could be used for vaccination program against potentially fatal endemic or emerging cholera caused by V. cholerae O139.